Carbon footprint calculator for children / Romiza Md Nor and Haleeda Azwa Abdul Hadi - Romiza, Md Nor; Haleeda Azwa, Abdul Hadi (2015)
Climate change is an environmental problem that is identified as a global issue which is closely linked with carbon dioxide emission. There are various ways to reduce the amount of CO2 emission. One of them is by increasing the knowledge among people especially youngsters who have less exposure about climate change. This paper investigates the effectiveness of using a medium which is an interactive web based carbon footprint calculator for kids called CFCkids. CFCkids is developed to allow children to calculate their carbon footprint based on their daily activities that contribute to the emission of carbon dioxide (CO2) for educational purposes. The calculation is divided into three parts which are home, school and tuition. CFCkids also provides information about climate change and tips to reduce carbon footprint. In testing phase, the pre and post-test on its usability and content had been conducted with children age ten to twelve years old. From the findings, it is discovered that CFCkids can increase the knowledge of children about climate change and how they can naturalize from the result of their carbon footprint calculation. This project is also relevant in becoming one of the educational mediums for them. For the future works of CFCkids, the system will be enhanced to allow children to connect with their friends using CFCkidsapplication which allows them to share their carbon footprint report to create awareness by looking into the impact of their own carbon footprint which can lead them to be more responsibletowards the environment.